Human Development and Economic Freedom: Empirical Evidence from the Great Lakes Region - Nzabirinda Etienne; Nkurunziza Joseph; Mugenzi Martin (المجلة الدولية للأداء الاقتصادي)
This study examines the impact of economic freedom on human development within the Great Lakes region. This region comprises the states of Burundi, the DRC, Rwanda, and Uganda. The data obtained from the World Bank's Prosperity Data 360 and the HDI from the United Nations Development Programme were employed for this research using fixed-effect panel data models and System GMM Two-Step models to determine the linkage between economic freedom and human development. The results depict a general positive relationship between economic freedom and human development across the region. Specifically, it is seen that economic freedom significantly correlates with human development, ranging from 1.12 in Uganda to 1.85 in Rwanda. HDI in all countries is positively related to human development with a coefficient of 0.13, while life expectancy contributes positively to human development in Burundi, DRC, and Uganda. Expected years of schooling and mean years of schooling are some of the educational indicators that also illustrate positive relationships with human development. Highly correlated to human development, Gross National Income per capita was 0.42 across all countries. The Democracy Index also shows a positive influence on human development, mainly in Burundi. From the System GMM model, it is confirmed that HDI, life expectancy, and GNI per capita significantly explain economic freedom. The findings show that though economic freedom and increase in income are important for development, governance, education, and healthcare reforms are fundamental for ensuring that growth in the region is inclusive and sustainable.